Heterogeneous photocatalytic degradation of 2‐chloro‐4‐nitrophenol using slurry and fixed bed reactor. Issue 2 (30th May 2014) - Verma, Anoop; Dixit, Divya; Toor, Amrit; Srivastava, Jayant
Abstract : This study is to see the heterogeneous photocatalytic degradation of 2‐chloro‐4‐nitrophenol in TiO2 slurry and fixed bed reactor. The catalyst was immobilized on different supports i.e., cemented beads, glass sheet, and sodium alginate balls. The dip coating method was used for the catalyst immobilization on the glass sheet and cemented slab, whereas in other case, physical entrapment of the catalyst slurry in the gel was used. The study includes photocatalytic degradation of 2‐chloro‐4‐nitrophenol along with process optimization by varying different parameters like pH, amount of photo catalyst, effect of H2 O2 concentration in suspension mode. Degradation observed was 86%, 72%, 75%, and 65% under suspension solar‐photocatalytic, glass‐plate solar reactor, coated cemented beads and immobilized sodium alginate balls, respectively at optimized conditions i.e. 4.5 pH and oxidant dose of 7.5 mM. Approximately 90% reduction in COD confirms the mineralization of the compound under study. Fixed bed photocatalysis would be more efficient and economical as filtering as well as recovery of the catalyst can be avoided. The application of solar powered photocatalytic reactors to treat waste water from different industries holds promise for regions receiving strong sunlight throughout the year, such as India. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 380–386, 2015